Effective strategies for enhancing English speaking competence among learners in English education study programs - Yuslinda Sari Zega (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2025)
This study aims to evaluate the English-speaking skills of 5th-semester Class B students enrolled in the English Education Study Program at the University of Nias. The main objective is to assess students’ speaking proficiency using a standardized speaking test assessment rubric and to classify their performance into various levels of competence. The evaluation focuses on determining the mean score, mode, and categorization of students’ speaking abilities to provide a clearer understanding of their proficiency distribution. A quantitative research method was employed in this study, involving 41 students as research participants. Data collection was conducted through a structured English-speaking test administered in an interview format. The test assessed several components of speaking competence, including fluency, pronunciation, grammar, vocabulary, and coherence. The results were then analysed statistically to determine overall performance trends. The analysis revealed a diverse range of speaking proficiency among the students. Out of the 41 participants, 5 students (12.2%) demonstrated very good speaking skills, 10 students (24.4%) were categorized as good, 25 students (61.0%) were identified as having sufficient proficiency, while only 1 student (2.4%) was categorized as insufficient. The mean score indicated a moderate level of overall proficiency among the class, while the mode score aligned with the “sufficient” category, indicating that this was the most common level among the group. The study concludes that while a majority of students possess adequate speaking skills, there remains significant room for improvement. These findings underscore the importance of differentiated instruction and targeted speaking activities to enhance language competence. Educators are encouraged to implement tailored pedagogical strategies that address the specific needs of learners across all proficiency levels. The results of this study provide valuable insights for curriculum developers and instructors seeking to improve spoken English instruction within similar academic contexts.